Functional Outcome of K-Wire Fixation of Supracondylar Fracture of Humerus (Type-III) in the Children Following Six Months - Mushtaq, Komal; Mehak, Shareen; Fatima, Laraib; Arshad, Humaira; Rehman, Muheebur; Saif, Kainat; Mateen, Aleena (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Supracondylar fracture is an injury to the humerus or upper arm bone just above the elbow. It is most common type of upper arm injury in children. Mostly caused by fall on outstretched elbow or direct blow to the elbow and mostly treated by k-wire in the children due to good results post-operatively. The objective of my study was to assess the functional outcome of k -wire fixation after supracondylar fracture of humerus (type-III) following six months. A descriptive case-series, a total sample of 20 cases of k-wire fixation after supracondylar fracture of humerus following six months in the children were included in the study, whose functional range were within 90-120 children of both sex, between age under 12 years were included. Study results showed 40% children with no difficulty, 45% with mild difficulty, and 15% with moderate difficulty. Overall, there were good functional outcome. The Current study concluded that, there was good Functional outcome of supracondylar fracture of humerus (type-III) with k-wire fixation following six months in children.